Leveraging Inventory Management for Enhanced Performance in Elementary School Cooperatives: Case Study from Majalengka Regency - Sutarman, Sutarman; Purnomo, Agus; Mety Zalynda, Putri (Jurnal Elementaria Edukasia, 2024)
Cooperatives play a significant role in promoting economic growth by not only increasing community income but also providing employment opportunities in the small business sector. For cooperatives to effectively support the economic development of villages, it is crucial for them to function as healthy business entities. One way to enhance their efficiency is by ensuring consistency in their managerial activities, ranging from planning to control, including inventory management. SD "X" Cooperative, located in Majalengka, engages in retail trading activities through a mini market. The cooperative deals with 19 specific types of items, which require strict inventory control. The governance process starts with determining the optimal quantity of economic orders to avoid shortages or excessive inventory of goods, thus ensuring satisfactory customer service. However, the cooperative currently faces challenges in terms of working capital shortage, hindering its ability to place orders according to the predetermined optimal quantity. Therefore, it becomes imperative to redefine the optimal order placement process by considering the available working capital. Such re-optimization will have an impact on increasing inventory costs, as the optimal order quantity decreases and the frequency of orders becomes more frequent. Despite the decrease in the optimal number of orders, the cooperative strives to fulfill customer demands while managing its limited working capital effectively